ADVANTAGES OF USING MUSIC AND SONGS IN ELT CLASSROOM - Koyshekenova, T.K. (SCIENCE and SOCIETY, 2023)
There are analyzed the importance of using music and songs in ELT classroom in this article. Music, songs and rhymes are effective teaching strategies which promote attention, memorization, artistic and musical taste. Such sort of entertainment may be appropriate for students’ learning process, subconscious, and fun and creates a positive atmosphere.